2009
DOI: 10.1614/ipsm-08-101.1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Carbohydrate and Nitrogen Concentrations in Oregon and California Populations of Brazilian Egeria (Egeria densa)

Abstract: Total nonstructural carbohydrate (TNC) reserves support growth, formation of reproductive structures, and sprouting of plant tissues, and nitrogen (N) is essential for amino acid synthesis and photosynthetic enzyme production. Timing of weed management to periods when these critical resources are most limiting might improve efficacy. We examined seasonal changes in carbohydrate and nitrogen concentrations in Brazilian egeria (Egeria densa), a common submersed aquatic weed, from two locations in the United Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Bold values represent the total area where the species was found in the fall and again in the summer Effects of invasive species on plant communities 451 constant flow (Pennington and Sytsma 2009). Thus, as native submersed plant species senesce in the fall, E. densa continues producing biomass, some of which persists through the winter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bold values represent the total area where the species was found in the fall and again in the summer Effects of invasive species on plant communities 451 constant flow (Pennington and Sytsma 2009). Thus, as native submersed plant species senesce in the fall, E. densa continues producing biomass, some of which persists through the winter.…”
Section: Discussionmentioning
confidence: 99%
“…Franks Tract), and these actions are likely to reduce areal cover of this species (Santos et al 2009) and could eventually change the composition back to a native species dominated community. Management of E. densa is complicated by its bimodal growth periods, late spring and autumn, (Pennington and Sytsma 2009), and by the large spatial extent of the Delta. This unique growth pattern would require multiple management actions throughout the year to overcome its competitive growth advantage, which would increase management costs substantially.…”
Section: Introductionmentioning
confidence: 99%
“…Total nonstructural carbohydrates (TNC) concentrations in rhizomes decreased with lower salinities (lower electrical conductivities), which could reflect the depletion of rhizome reserves due to growth stimulation under brackish conditions, where S. densiflora has been described as a highly competitive species (Costa et al 2003). Depletion of carbohydrate reserves during rapid growth has been reported in several other submersed and emergent aquatic plants such as Phragmites australis (Granéli et al 1992;Č ižková et al 2001), Egeria densa (Pennington and Sytsma 2009), and Myriophyllum spicatum (Perkins and Sytsma 1987;Madsen 1997). Rhizome dynamics are very important in salt marsh development in a changing world since rhizome accumulation is key to maintaining soil volume with b Fig.…”
Section: Discussionmentioning
confidence: 97%
“…By understanding the phenology of the target plant and the fate of carbohydrates, there is the possibility to identify any potential "weak points" in the life cycle. Previous research on other plant species has demonstrated successfully that timing the control technique to the target plant's low point in carbohydrate storage can increase the effectiveness of management (Richburg 2005;Pennington & Sytsma 2009).…”
mentioning
confidence: 99%